(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2025)
The trace formulas of linear differential operators deeply reveal the structure of the spectrum of differential operators and have important applications in the numerical calculation of eigenvalues, the theory of inverse problems, and the theory of solitons. For the first time in work [1], a regularized trace for the Sturm-Liouville operator is calculated. This result was generalized by many authors, and methods were developed for generalizing this formula to the case of other operators [2-4]. The trace formulas for the conformable fractional Sturm-Liouville problem was studied in [5].